A Re‐examination of Analyst Under‐reaction1. (16th October 2013) - Baik, Bok; Lee, Su Jeong
Abstract Prior studies suggest that analysts under‐react to past information (Klein, 1990; Abarbanell and Bernard, 1992; Easterwood and Nutt, 1999). We examine whether evidence interpreted as analyst under‐reaction to negative news can be attributed to analyst self‐selection. Analyst self‐selection arises when analysts' information production efforts are focused toward stocks that analysts expect to perform well. Using a large sample of firms for the period of 1983–2004, we find evidence suggesting that self‐selection is responsible, at least in part, for analyst under‐reaction to past negative information about the firm's performance.